(untitled) (Educational Knowledge, 2022)
This article deals with the serious problem of violence in the family and highlights the main role of education in its prevention, as well as in addressing its consequences. Methodologically, this work is based on the documentary review method, in order to obtain consistent knowledge about the phenomenon studied; synthesize it, interpret it and subsequently offer guidelines for action. It can be said that a well-executed review as a research method creates a solid foundation for advancing knowledge, and facilitates theoretical development with a practical scope (Webster & Watson, 2002). For this reason, various guidelines collected by the World Health Organization (WHO) and the Pan American Health Organization (PAHO) were reviewed in their Report entitled Prevention of violence: the evidence (2013). There are seven strategies aimed at preventing interpersonal violence that, with pedagogical commitment, are adapted and taken as references for the prevention of violence in the family. The study of this document is complemented by the review of other sources and research.